ANALISIS YURIDIS PEMBERIAN IWADH DALAM GUGATAN CERAI MENURUT HUKUM ISLAM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NO.248/K/AG/2011) - MASWIWIN MASWIWIN (PREMISE LAW JURNAL, 2016)
Allah SWT determines the marriage whose aim is to realize the peace of life. Islam does not allow the painful life of a husband and a wife to occur. It is possible that they may to break the marriage tie in a good way with a consideration for the good of each other's lives. A divorce is not only due to husband’s willingness (talak divorce), but also because of the wife's request (claimed divorce). Based on the research results, the legal basis of iwadh payment in khulu’ divorce according to the Islamic Fiqh is the Allah’s words in the Koran in Al-Baqarah verse 229.  The legal basis of iwadh payment in khulu’ divorce according to the Islamic Fiqh is the Allah’s words in the Koran in Al-Baqarah verse 229. The legal consequence after his wife paid iwadh was she got talak bain. The judge’s legal concideration to decide the case No.248/K/AG/2011 was surah An-Nisa verse 12. Keywords: Iwadh Payment, Divorce Claim, Islamic Law